Clickable Substrate Mimics Enable Imaging of Phospholipase D Activity - Bumpus, Timothy W. (ACS Cent Sci, 2017)
[Image: see text] Chemical imaging techniques have played instrumental roles in dissecting the spatiotemporal regulation of signal transduction pathways. Phospholipase D (PLD) enzymes affect cell signaling by producing the pleiotropic lipid second messenger phosphatidic acid via hydrolysis of phosphatidylcholine. It remains a mystery how this one lipid signal can cause such diverse physiological and pathological signaling outcomes, due in large part to a lack of suitable tools for visualizing the spatial and temporal dynamics of its production within cells. Here, we report a chemical method for imaging phosphatidic acid synthesis by PLD enzymes in live cells. Our approach capitalizes upon the enzymatic promiscuity of PLDs, which we show can accept azidoalcohols as reporters in a transphosphatidylation reaction. The resultant azidolipids are then fluorescently tagged using the strain-promoted azide–alkyne cycloaddition, enabling visualization of cellular membranes bearing active PLD enzymes. Our method, termed IMPACT (Imaging Phospholipase D Activity with Clickable Alcohols via Transphosphatidylation), reveals pools of basal and stimulated PLD activities in expected and unexpected locations. As well, we reveal a striking heterogeneity in PLD activities at both the cellular and subcellular levels. Collectively, our studies highlight the importance of using chemical tools to directly visualize, with high spatial and temporal resolution, the subset of signaling enzymes that are active.